The imbalance case in multilingualism practices at Pesantren: Students’ voices - Muhammad, Faiz Rizki; Purbani, Widyastuti (CV. Yudhistt Fateeh, 2024)
Today, multilingualism is extremely common. In the Indonesian context, it has its own phenomenon in which the Indonesian and English languages coexisted and frequently earned special emphasis among the mother tongues of each region. Surprisingly, multilingualism has been practiced in pesantren for a long time, with Arabic becoming the primary choice alongside Indonesian and regional languages. Now, Pesantrens are currently developing and adding more languages as learning targets, including English. However, according to the authors’ preliminary research at several renowned pesantren, English has not yet surpassed Arabic in terms of its practice in their daily usage. In fact, pesantren is an ideal setting for language environmental conditioning using the Multilingual Education technique. The purpose of this study is to investigate the causes of the language imbalance as viewed through the students' perspectives and how they influence the students’ language behavior. The authors utilized a descriptive qualitative method to analyze data gathered from interviews with 40 grade X-XII students at two Pesantrens in Central Java and Yogyakarta. The recorded data was then analyzed using framework analysis method. The results showed 5 main factors from the case: 1) students’ anxiety, 2) lack of language exposure, 3) unsupporting language environment, 4) students’ religious identity, and 5) students’ future needs. There were also different perceptions between Arabic as a language for studying religion and worship, while English only means for communication and preparation to advanced study. These findings also concluded that these perceptions influence their imbalance in multilingualism practices.